2017
DOI: 10.1111/head.13183
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Headache: A Cross‐Sectional Study

Abstract: HIV-positive patients had a high frequency of headaches, which had a great impact on patients' lives. The pattern most often found was migraine. There was no correlation between CD4 counts and the severity of headaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
2
8
1
1
Order By: Relevance
“…Headache was associated with impaired functional status and significant headacheassociated disability in this cohort, similar to other studies in Africa (Woldeamanuel, Andreou et al 2014, Morgan, Eguia et al 2015, Zebenigus, Tekle-Haimanot et al 2017 and in HIV+ cohorts (Kirkland, Kirkland et al 2012, Sampaio Rocha-Filho, Torres et al 2017. A study in Zambia reported headaches led to lost working days which they estimated accounted for a loss in the national gross domestic product of nearly 2% .…”
Section: Discussionsupporting
confidence: 82%
“…Headache was associated with impaired functional status and significant headacheassociated disability in this cohort, similar to other studies in Africa (Woldeamanuel, Andreou et al 2014, Morgan, Eguia et al 2015, Zebenigus, Tekle-Haimanot et al 2017 and in HIV+ cohorts (Kirkland, Kirkland et al 2012, Sampaio Rocha-Filho, Torres et al 2017. A study in Zambia reported headaches led to lost working days which they estimated accounted for a loss in the national gross domestic product of nearly 2% .…”
Section: Discussionsupporting
confidence: 82%
“…Migraine-like headaches have already been described in association with viral infections (2226). For our patients who experienced previous migraines, the headache they experienced associated with COVID-19 was most often of a migraine phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Stress during COVID-19 could be a trigger of migraine attacks and may have a role in this worsening. In the other hand worsening of primary headaches could be explained by viral diseases [ 16 ].…”
Section: Discussionmentioning
confidence: 99%